2004
DOI: 10.1097/01.asn.0000102471.89084.8b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early and Late Intervention with Epoetin α on Left Ventricular Mass among Patients with Chronic Kidney Disease (Stage 3 or 4)

Abstract: Abstract. It is not known whether prevention of anemia among patients with chronic kidney disease would affect the development or progression of left ventricular (LV) hypertrophy. A randomized controlled trial was performed with 155 patients with chronic kidney disease (creatinine clearance, 15 to 50 ml/min), with entry hemoglobin concentrations ([Hb]) of 110 to 120 g/L (female patients) or 110 to 130 g/L (male patients). Patients were monitored for 2 yr or until they required dialysis; the patients were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
115
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(131 citation statements)
references
References 45 publications
14
115
1
1
Order By: Relevance
“…However, on balance, among randomized controlled trials of dialysis patients, there has been no demonstration of an impact of normalization of Hgb with ESA on CVD events or survival (20)(21)(22)(23)(24)(25); moreover, many of these studies have raised questions of harm (vascular access thrombosis and stroke), which have not been definitively addressed. Smaller randomized trials among nondialysis patients have also failed to show improvements in surrogate end points for CV outcomes (left ventricular mass index on echocardiography and decline in GFR) among ESA-treated patients (26)(27)(28)(29). Recent larger randomized clinical trials have had variable and somewhat conflicting results.…”
Section: Trials Of Hgb Normalization and Cardiovascular Outcomesmentioning
confidence: 99%
“…However, on balance, among randomized controlled trials of dialysis patients, there has been no demonstration of an impact of normalization of Hgb with ESA on CVD events or survival (20)(21)(22)(23)(24)(25); moreover, many of these studies have raised questions of harm (vascular access thrombosis and stroke), which have not been definitively addressed. Smaller randomized trials among nondialysis patients have also failed to show improvements in surrogate end points for CV outcomes (left ventricular mass index on echocardiography and decline in GFR) among ESA-treated patients (26)(27)(28)(29). Recent larger randomized clinical trials have had variable and somewhat conflicting results.…”
Section: Trials Of Hgb Normalization and Cardiovascular Outcomesmentioning
confidence: 99%
“…Beginning with the clear association between higher Hb levels and better outcomes and the hypothesis that this may be due to the deleterious effect of anemia on the development of LVH or simply a marker of greater morbidity (mainly inflammation), a number of clinical studies were designed to test whether correcting anemia can reverse LVH and improve patient outcomes. Taking LVH as an intermediate outcome rather than a surrogate end point, data from mainly small and uncontrolled studies indicated that correcting anemia led to partial LVH regression (16 -20), but larger randomized studies failed to confirm that randomization to the higher Hb levels that were obtained using recombinant human erythropoietin had a significant positive effect on patients who were not (21,22) and were (23) on dialysis.…”
Section: Anemia Correction and Outcome Improvementmentioning
confidence: 99%
“…The clinical benefits and adverse effects associated with normal or near normal hemoglobin values were evaluated in multiple randomized studies that assessed mortality and morbidity from cardiovascular or cerebrovascular events, good control of blood pressure, quality of life, functional status and vascular access thrombosis [71,[118][119][120][121][122][123][124][125][126] . The results of these studies have not suggested any improvements after correction of anemia, except in quality of life.…”
Section: Hemoglobin Targetmentioning
confidence: 99%